(untitled) (Panacea Journal of Medical Sciences, 2022)
Introduction: Vitamin B12 deficiency (VBD) Megaloblastic Anemia (MA) is a relatively common disease encountered by pediatricians in Jammu region of north India, yet the data on prevalence of VBD in this age group remains scarce. Hence this study was conducted to study the prevalence and clinic hematological profile of VBD associated MA in children between 6 months to 18 years of age. Aim: To estimate the prevalence and clinico hematological profile of vitamin B12 deficiency associated MA in children between 6 months to 18 years, who were admitted in SMGS Hospital, Government Medical College Jammu. Materials and Methods: A Retrospective cross sectional study was conducted in children between 6 months to 18 years, who were admitted in SMGS Hospital, Government Medical College Jammu with diagnosis of Nutritional Anemia from April 2020 - March 2021.Case records of patients were reviewed for vitamin B12 deficiency as a cause of MA who were included in study. Vitamin B12 deficiency was diagnosed by measuring B12 levels in blood and by bone marrow examination if required. Clinic hematological profile of the participants was observed by reviewing their records for age, sex, socioeconomic status, food habits, presenting complaints, clinical signs and symptoms, peripheral smear findings and need for transfusion. All descriptive data collected was represented by tables and evaluated for statistical outcomes. Results: The prevalence of vit. B12 deficiency associated MA in our study is 16.66 %. Among them 60% were females and 40% males. Age wise distribution was 6months -1 year 20 %, 1-5 years 22%, 6-10years 16% and 11-18 years was 42%. Vitamin B12 deficiency was more prevalent in lower socioeconomic group 80% and in those who were vegetarians 60%. Anorexia, generalised weakness, pallor was observed in 100% subjects. Neurologic involvement in the form of irritability, tremors was present in 30%. Icterus was seen in 10% while hepatomegaly and splenomegaly was present in 20 % and 22% respectively. Edema was seen in 2% of the subjects. Hyperpigmentation of knuckles was observed in 86% of the patients. Macrocytic anemia (MCV >100 ug/L) was observed in 100%. Bicytopenia was seen in 80% while Pancytopenia was present in 20%. Among 150 cases of Megaloblastic Anemia 80% of the patients were diagnosed by Vitamin B12 essay, 20% were diagnosed by Bone marrow examination. Blood transfusion secondary to severe anemia was required in about 10%. Conclusion: Vitamin B12 deficiency is not that uncommon in our population with prevalence of 16.66% in hospitalized children. However true prevalence can only be estimated by population based surveys in pediatric age group. The most common presenting complaint in Megaloblastic Anemia is anorexia, generalised weakness, irritability manifesting clinically as pallor, hyperpigmentation of knuckles and hematologically as macrocytic anemia with 80% bicytopenia and 20% pancytopenia. Thus vitamin B12 addition in anaemia control and prophylaxis programmes may be considered.